ANALYZING THE RELATIONSHIP BETWEEN KNOWLEDGE, ATTITUDE, AND BULLYING BEHAVIOR AMONG ADOLESCENTS AT SENIOR HIGH SCHOOL 5 SURAKARTA - Sugiarti, Ika; Putra, Firdy Rama Permana; Afriyanto, Dzul Fahmi (Jurnal Kesehatan Kusuma Husada, 2025)
Background: According to data from the Central Bureau of Statistics (BPS), a total of 1,427 cases of violence against children under the age of 18 occurred. One of the most common forms of violence in the school environment is bullying, particularly in the form of verbal teasing, with a prevalence of up to 75% among students. However, only 45% of victims are willing to report such incidents. Bullying behaviour is influenced by factors such as knowledge and attitude. The research objective is to identify the correlation between knowledge and attitudes toward bullying behaviour among SMA Negeri 5 Surakarta students.Methods: A correlational quantitative approach was used in this research. The population consisted of all 128 tenth-grade students, and 97 respondents were selected using simple random sampling based on the Slovin formula. The independent variables were knowledge and attitude, while the dependent variable was bullying behaviour. Data were collected using questionnaires and analysed using the Chi-square statistical test.Results: The analysis showed no significant correlation between the level of knowledge and bullying behaviour (p-value = 0.983), and no significant correlation between attitude and bullying behaviour (p-value = 0.363).Conclusion: Furthermore, most students reported never engaging in bullying, totalling 93 respondents (95.9%). There was no significant relationship between knowledge and bullying behaviour, with a p-value of 0.569 > 0.05. Similarly, there was no significant relationship between attitudes and bullying behaviour, with a p-value of 0.827 > 0.05.